Non-governmental organizations coalition in influencing global agenda - Anthony Eniayejuni; Shona Olalere; Eugene Obiora Eugene (Faculty of Social and Political Science, Universitas Airlangga, 2022)
This study aims to show how a coalition of non-governmental organizations (NGOs) can influence the human rights agenda. This study relies on the advocacy coalition Framework (ACF) assumption that multiple varieties of actors involved in the policy process may combine to form coalitions. This study examines how Amnesty International (AI), Human Rights Watch (HRW), and the International Crisis Group (ICG) formed a coalition to advocate for measures to address humanitarian crises in Sri Lanka and Darfur. This study employed qualitative research methods and relied on secondary sources related to the topic. The findings show that a coalition formed by human rights organizations can influence policies adopted by the international community and can also influence actions taken by national communities. This study concludes that just as states need to form a coalition with other states or work as “allies” to promote human rights on a national and global level, NGOs also function in a similar manner.